ATHB2 is a negative regulator of germination in Arabidopsis thaliana seeds - Tognacca, Rocío Soledad (2021)
The germination timing of seeds is of the utmost adaptive importance for plant populations. Light is one of the best characterized factors promoting seed germination in several species. The germination is also fnely regulated by changes in hormones levels, mainly those of gibberellin (GA) and abscisic acid (ABA). Here, we performed physiological, pharmacological, and molecular analyses to uncover the role of ATHB2, an HD-ZIP II transcription factor, in germination of Arabidopsis seeds. Our study demonstrated that ATHB2 is a negative regulator and sustains the expression of transcription factors to block germination promoted by light. Besides, we found that ATHB2 increases ABA sensitivity. Moreover, ABA and auxin content in athb2-2 mutant is higher than wild-type in dry seeds, but the diferences disappeared during the imbibition in darkness and the frst hours of exposition to light, respectively. Some ABA and light transcription factors are up-regulated by ATHB2, such as ABI5, ABI3, XERICO, SOMNUS and PIL5/PIF1. In opposition, PIN7, an auxin transport, is down-regulated. The role of ATHB2 as a repressor of germination induced by light afecting the gemination timing, could have diferential efects on the establishment of seedlings altering the competitiveness between crops and weeds in the feld.